Study on the Bearing Plate of Steel Clarification Tank under Earthquake - Cheng, Xiwei; Cheng, Chuyun; Zhang, Wanlin; Hu, Lankai; Cheng, Xuansheng (Shock and Vibration, 2023)
The stress at the support structure of the clarification tank is large, which will have a certain impact on the whole clarification tank structure. The typical stress concentration phenomenon will cause structural damage and serious harm to the steel clarification tank itself. In order to study the influence of the bearing plate on the seismic response of steel clarification tank, this paper analyzes the dynamic response of the clarification tank by setting different thickness bearing plates at the connection between the steel column and the structure body of the steel clarification tank. Based on the displacement, stress, and liquid sloshing height of the steel clarification tank, the thickness of the bearing plate is obtained. The results show that the maximum stress of the steel clarification tank under different seismic waves decreases with the increase of the thickness of the bearing plate. The thickness of the bearing plate has a certain influence on the maximum displacement of the clarification tank structure, but the increase in the thickness of the bearing plate does not necessarily reduce the maximum displacement. Different bearing plate thicknesses have no effect on the position of displacement, and the maximum displacement occurs at the top of the outer wall.